Prevalence and causes of cesarean births among women residing at high altitude in Lhasa, Tibet: A retrospective observational study of 7365 women - Yuan-Yuan Zheng; Zhuo-Ma Pubu; Yang Ge; Zhuo-Ma Bianba; Xiao-Hong Xu (Elsevier, 2019)
Objective: Currently, there is paucity of data on the rate of vaginal deliveries and cesarean section among women in Tibet. In this study, we carried out an observational study of 7365 consecutive pregnant women in Lhasa, Tibet who gave birth at our tertiary care institution between 2012 and 2015. Materials and methods: In this retrospective study, we reviewed the hospital records for demographic data, obstetric history, and the number of vaginal and emergency cesarean section deliveries. The overall and annual rate of vaginal and cesarean section deliveries was calculated. Causes, indications or risks for cesarean section were also analyzed. Results: During the review period, 7365 neonates were delivered at our hospital, including 1690 (23.0%) deliveries via cesarean section. The yearly rate of cesarean section progressively declined from 26.7% in 2012 to 18% in 2015 (P < 0.001). Furthermore, the annual rate of emergency cesarean section declined 53.9%between 2012 and 2015(P < 0.001). Fetal risk factors (39.9%) and maternal risk factors (40.3%) were the major causes of cesarean section in the women. Social factors as a cause of cesarean section fluctuated between 7.9% and 11.1%. Conclusion: This study has demonstrated a steady decline in the annual rate of cesarean section in women in Tibet between 2012 and 2015. A decrease in the rate of emergency cesarean section contributed substantially to this decline. Moreover, approximately 10% caesarian sections were performed without clear indications, highlighting the need for strengthening prenatal counseling for pregnant women in Tibet. Keywords: Cesarean section rate, Cesarean indication, Plateau area